Genome-Wide Analyses of Subtilisin-Like Serine Proteases on Solanum tuberosum - Norero, Natalia Sigrid (2016)
Plant subtilisin-like serine proteases or subtilases constitute a large expanded gene subfamily in potato. We identified 82 potato subtilases encoded by 74 genes. All subtilases present a characteristic S08 domain, and the majority of them have an association protein domain, an inhibition_I9 domain and a signal peptide that consists of a signal sequence for targeting to the secretory pathway. Phylogenetic studies revealed five subtilase groups named StSBT1 to StSBT5. A genome expansion of potato subtilase subfamily was reflected in two phylogenetic clusters, StSBT1 and StSBT4 both characterized by intronless genes in tandem arrays mainly in chromosome I and VIII. Twenty nine of the identified subtilases co-localize with six out of 24 metaQTLs related to late blight resistance previously described in potato. These metaQTLs includes subtilase genes up regulated in detached potato leaves inoculated with P. infestans, some of which are homologous to p69 subtilases genes from tomato.